2004
DOI: 10.1155/2004/748685
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Cancer Pain Management Knowledge and Attitudes of British Columbian Physicians

Abstract: INTRODUCTION: There are many potential barriers to adequate cancer pain management, including lack of physician education and prescription monitoring programs. The authors surveyed physicians about their specific knowledge of pain management and the effects of the regulation of opioids on their prescribing practices. METHODS: A questionnaire was mailed out to British Columbia physicians who were likely to encounter cancer patients. The survey asked for physicians' opinions about College of Physicians and Surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
2
11

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 17 publications
4
36
2
11
Order By: Relevance
“…Pain causes an increase in the sympathetic response of the body with subsequent rise in heart rate, cardiac work, difficulty in breathing and oxygen consumption. Prolonged pain can reduce physical activity and lead to venous stasis and an increased risk of deep vein thrombosis and consequent pulmonary embolism (American Society of Anesthesiologists Task Force on Acute Pain, 2012; Gallagher et al, 2004). However, many researchers reported that unsatisfactory pain management were practiced in different countries (Taylor et al, 2008;Rejeh et al, 2008;Windsor et al, 1996).…”
Section: Author(s) Agree That This Article Remain Permanently Open Acmentioning
confidence: 99%
“…Pain causes an increase in the sympathetic response of the body with subsequent rise in heart rate, cardiac work, difficulty in breathing and oxygen consumption. Prolonged pain can reduce physical activity and lead to venous stasis and an increased risk of deep vein thrombosis and consequent pulmonary embolism (American Society of Anesthesiologists Task Force on Acute Pain, 2012; Gallagher et al, 2004). However, many researchers reported that unsatisfactory pain management were practiced in different countries (Taylor et al, 2008;Rejeh et al, 2008;Windsor et al, 1996).…”
Section: Author(s) Agree That This Article Remain Permanently Open Acmentioning
confidence: 99%
“…In a similar study, surgeons had the lowest scores in knowledge of cancer-related chronic pain management. 5 There is little known regarding the quality of training in pain management for residents in surgery programs in general or urology specifically. The goal of this study was to gain a deeper understanding of the type and quality of education we are providing to residents in urology, by exploring their attitudes and experiences in acute and chronic pain management during their training.…”
Section: Introductionmentioning
confidence: 99%
“…Die inhaltliche Entwicklung der Fragen orientierte sich dabei im Wesentlichen an häu-fig auftretenden Kenntnislücken, wie sie in früheren Arbeiten beschrieben wurden [14,16,25,30,33,41,43] und wie sie sich aus der eigenen klinischen Arbeit im Rahmen einer universitären Schmerzambulanz ergaben. Darüber hinaus wurden als praxisrelevant erachtete Themenbereiche aus der Literatur mit einbezogen [13,20,21,37,38,42] …”
Section: Methodikunclassified
“…Diese extrem niedrige Quote richtiger Antworten leitet sich vermutlich von der Komplexität der Frage her. Während andere Untersuchungen z. T. mit einem einfachen Multiple-Choice-Design oder der Bewertung von vorgegebenen Aussagen arbeiteten [14,43], stellte die offene Frage in dieser Erhebung mit der erforderlichen Nennung eines Präparates, einer Dosierung und eines Einnahmeschemas den Interviewten vor eine schwierigere, aber auch praxisrelevantere Aufgabe. Dass sich die hier gemachten Beobachtungen auch in der täglichen Praxis widerspiegeln, zeigt eine Anwendungsbeobachtung zu Fentanyl TTS aus dem Jahr 2001.…”
Section: Diskussionunclassified